2012
DOI: 10.1021/jf302881t
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Carnosic Acid, Carnosol, and Rosmarinic Acid Concentrations in the in Vitro Antioxidant and Antimicrobial Activities of Rosmarinus officinalis (L.) Methanolic Extracts

Abstract: The importance of the diterpenic and rosmarinic acid content in the biological activities of rosemary extracts has been studied previously, but how the relationship between the concentration of these components affects their antioxidant and antibacterial activities has received little attention. Accordingly, from a total of 150 plants, 27 methanolic extracts were selected, for their similar diterpene contents but different ratios between carnosic acid and carnosol concentrations. In extracts with similar rosma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 47 publications
4
77
1
3
Order By: Relevance
“…Other studies associated antimicrobial activity to phenolic substances (Jordan et al, 2012;Jaberian et al, 2013), which could elucidate the better antimicrobial activity of these extracts, as the HPLC/MS analyses displayed largest quantities of carnosic acid for the extracts harvested in October/2012 and January/2013. On the other hand, Salmonela and E. coli stood very resistant to rosemary samples, which could be attributed to the presence of the lipid bilayer at the cell wall of the gram-negative bacteria, as they avoid that the components reach the cytoplasmic membrane and cause destructive action inside of the cell.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Other studies associated antimicrobial activity to phenolic substances (Jordan et al, 2012;Jaberian et al, 2013), which could elucidate the better antimicrobial activity of these extracts, as the HPLC/MS analyses displayed largest quantities of carnosic acid for the extracts harvested in October/2012 and January/2013. On the other hand, Salmonela and E. coli stood very resistant to rosemary samples, which could be attributed to the presence of the lipid bilayer at the cell wall of the gram-negative bacteria, as they avoid that the components reach the cytoplasmic membrane and cause destructive action inside of the cell.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…RosmA possesses anti-inflammatory (Chu et al, 2012;Jiang et al, 2009;Ku et al, 2013), antioxidant (Domitrović et al, 2013;Gao et al, 2005;Zdarilová et al, 2009), anticancer (Moon et al, 2010;Scheckel et al, 2008;Xu et al, 2010), and antimicrobial (Jordán et al, 2012;Suriyarak et al, 2013) activities. Moreover, RosmA has been reported to have neuroprotective effects on the rat brain after acute ischemic damage.…”
Section: Introductionmentioning
confidence: 99%
“…They associated the activity of the extract with the carnosic acid content as they found that the fraction that was richer in (mainly composed by) carnosic acid presented the highest MIC against S. aureus and E. coli. Jordán MJ et al [17] showed in their research that high content of carnosol in relation to carnosic acid improved the antimicrobial activity of rosemary methanolic extracts against L. monocytogenes and S. aureus. Garlic SCFE was also able to inhibit the growth of all strains tested.…”
Section: Antimicrobial Activity Of Scfesmentioning
confidence: 99%
“…In the same line, Muñoz M et al [6] determined the effect of different plant SCFEs on the growth of L. monocytogenes and found that rosemary extract was the most effective (compared to oregano and laurel SCFE), reducing counts even below the detection limit. The activity or rosemary SCFE has been related with the presence of active compounds like carnosic acid, camphor, carnosol, borenol, 1,8-cineole, alfa-pinene [16,17]. In their work Ramírez P et al [18] evaluated the antimicrobial activity of rosemary SCFE and the three different fractions obtained by SCF fractionation process; besides, the composition of the extract and every fraction collected was analysed by gas chromatography.…”
Section: Antimicrobial Activity Of Scfesmentioning
confidence: 99%